Affective temperament in students of musical professions. A preliminary report - Jaracz, Katarzyna; Jaracz, Marcin (Journal of Education, Health and Sport, 2019)
Introduction and aim of the study Affective temperaments are associated with predisposition to affective disorders. In mild, sub-clinical form, they are widely distributed in the population and have adaptive qualities, for example, constitute the predisposition to perform specific professions. The aim of the present study was to assess the affective temperament among students of the vocal and acting department of a music university. Material and methods 31 students aged 21-30 participated in the study. Affective temperament was assessed by means of the TEMPS-A questionnaire. Results Comparison of the intensity of particular affective temperaments showed higher, in comparison to other dimensions, intensity of hyperthymic temperament. The group also showed higher rates of hyperthymic, compared to irritable temperament. The rates of anxious temperament were negatively correlated with age. Conclusions Students of the vocal and acting department of the music university present a specific profile of affective temperament, which is associated with both predispositions to perform the singing profession and the risk of affective disorders.